Analisis Iklim Sekolah Penggerak dalam Menunjang Pembelajaran dengan Paradigma Baru - Saiya, Kezia Y; Kempa, R; Ratumanan, Tanwey Gerson (Jurnal Paedagogy, 2023)
This research aims to analyze the driving school climate, including physical, social, and academic dimensions, in supporting learning with a new paradigm. This research method used a descriptive method with a qualitative approach. The research was conducted at Xaverius Ambon Private High School, involving 16 informants: the principal, teachers, students, education staff, and committee. The data analysis technique for this research used interactive analysis, including data reduction, data presentation, and drawing conclusions. The research results were as follows: 1) in the physical dimension of schools (facilities and infrastructure), there were still limitations: WIFI and Infocus networks, which sometimes experience problems, some infrastructure did not yet have a special room, limited space for movement. 2) in the social dimension of the school, the implementation of the 7-character values of Xavier College and the application of school culture are the basis for every policy and interpersonal relationship built between school members. 3) in the academic dimension, there was learning progress with a new paradigm entering the 2nd year to become a driving school where SMAS Xaverius also pays attention to the quality of learning, high expectations, and learning evaluation.